Research progress of gene editing technology CRISPR/Cas9 system in animal gene editing - Feng Fan; Kang Mengna; Zhu Xiaolan; Cao Weiping; Liu Yueqin; Chen Qi; Lin Fangfang; Qianfu Yanwen; Xu Wenlina (International Journal of Veterinary Science and Research - Peertechz Publications, 2018)
Gene editing technology, from the beginning of RNA interference (RNAi) technology to efficient developed enzyme technology, has been widely used in recent years. These efficient enzyme technologies include zinc finger nuclease (ZFN) technology, transcriptional activation-like effector nuclease (TALENs) technology, and clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated (Cas) 9 system (CRISPR/Cas9) technology. The CRISPR/Cas (Cas) system is a gene editing tool for DNA modification regulated by a short RNA and is a new type of genome editing tool that is faster, more efficient, and more accurate than the zinc finger nuclease and transcription activator-like effector nuclease. This article reviews the structure and function of the CRISPR/Cas system, and is aimed to outline the Cas9 design strategy, factors that affect the Cas9 gene editing efficiency, off-target detection and analysis methods, and especially the application in animal gene editing studies. Based on CRISPR/Cas9 gene editing has been successfully implemented in a variety of animals, and it is expected to become a new feasible way to establish animal models and study disease prevention in veterinary science and research.